Qualidade de vida em Tupaciguara - MG: diretrizes e novos rumos para o planejamento urbano - Silva, Maraísa Costa da (2016)
The aim of this study is to analyze the life’s quality at Tupaciguara-MG and to propose guidelines for urban planning. One of the specific objectives, is to know the socialenvironmental reality at Tupaciguara. Other objective is to analyze the life’s quality at the city and discuss urban planning focused on life’s quality. The study began with literature review; about urbanization, city planning and urban life’s quality, sustainable cities healthyand small town. A diagnosis to know the city was done based on the bibliographic discussion, focusing on urban area, since its formation, the socio-spatial context of population, environmental conditions, and socio-spatial analysis, economics, housing, urban and planning management. In addition to this, a comparative analysis of quality of life was made with municipalities at Triângulo Mineiro/Alto Paranaíba-MG region, those which have total population between 10,000 to 30,000 inhabitants. Afterwards was discussed about planning at Tupaciguara with proposals of guidelines. At first result was made a description of positives and negatives points, which supported in the formulation of the FOFA (COLOCAR O QUE SIGNIFICA), what says the priority actions, including the most appropriate management of the environmental area of Tupaciguara. At second result was highlighted the present and intended scene that formed the guidelines table. Concluding life’s quality is median at Tupaciguara, what requires bigger attention with environmental and health area, to improve the life’s quality for the population.